An entrepreneurship education, training and support framework for South African architects - Vosloo, C.; Vosloo, P.; Antonites, A. (South African Journal of Higher Education, 2019)
This article will report the findings of a study undertaken to propose an integrated education and training framework that can enhance the entrepreneurial performance of South African Architects’ firms while contributing to the current discourse on entrepreneurial education and training. Many South African architects’ firms are finding it difficult to stay afloat (Corbert 2015, 44). While there could be many reasons for this situation, the absence of appropriate entrepreneurship education, training and support for architects could be a contributing factor. Substantial agreement exists amongst entrepreneurial education and training theorists that a phased approach that includes enacted learning is best suited for entrepreneurship education and training. Hence the article proposes a framework as a basic conceptual structure within which the education and training can be packaged. The study used a mixed methods approach as a single source was insufficient and, due to the use of multiple phases or projects, could best achieve the overall research objective (Creswell & Plano-Clark 2011, 8). The purpose of the article is to bring the findings and recommendations to the attention of those who can put them into effect and to contribute to the discourse on entrepreneurship education and training.